Impact of diabetes mellitus on tuberculosis drug resistance in new cases of tuberculosis. (March 2016) - Baghaei, Parvaneh; Tabarsi, Payam; Javanmard, Pedram; Farnia, Parissa; Marjani, Majid; Moniri, Afshin; Masjedi, Mohammad Reza; Velayati, Ali Akbar
Highlights: Multidrug-resistant tuberculosis was more prevalent in TB patients with diabetes mellitus (DM). DM-TB patients are at increased risk of anti-TB drug resistance. Age <40 years and history of TB contact were other risk factors for TB drug resistance. Sex and cavitary lesions did not affect TB drug resistance. Abstract: The objectives of this study were to determine the impact of diabetes mellitus (DM) on antituberculosis drug resistance in new cases of tuberculosis (TB). A case-control study was conducted on all newly diagnosed pulmonary TB adult patients with DM as cases and without DM as controls who were hospitalised from May 2013 to October 2013 in Iran. A molecular resistance test for rapid detection of resistance to isoniazid and rifampicin was done. Multivariate analysis was performed to determine the impact of DM on any anti-TB drug resistance. In total, 62 TB cases with DM and 64 TB cases without DM were included. TB cases with DM were more likely to be older (59 years vs. 43 years; P  = 0.001). Two TB-DM patients had multidrug-resistant TB (MDR-TB) (3.2%) compared with no cases of MDR-TB in the control group, and more TB-DM cases had isolates that were resistant to at least one drug (12.9% vs. 10.9%). DM [odds ratio (OR) = 4.82, 95% confidence interval (CI) 1–23.57], age <40 years (OR = 5.48, 95% CI 1.19–25.29) and history of TB contact (OR = 5.86, 95% CI 1.69–20.36) remained significantly associated with any drug resistance in the multivariate analysis. In conclusion, new TB patients with DM are at increased risk of anti-TB drug resistance. More studies are needed to confirm these results.